Pap smear in antepartum women: an opportunity to screen and create awareness - Ethirajan, Shanthi; R., Srinidhi; K., Jayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cervical and breast cancers are the leading malignancies in females in India. Cancer cervix is preventable and treatable if detected at premalignant stage. Pap smear is a recommended screening method for cancer cervix and its precursors. Pap smear screening in antenatal period presents an opportunity to screen for premalignant cervical lesions and genital infections. This study was undertaken to determine the prevalence of abnormal cervical smears and genital infections among antenatal women. Methods: It is a prospective study in which, 200 antenatal mothers at booking visit, were included in the study. Details on their demographic characteristics, obstetric profile, and past history of Pap test were collected. Liquid based cytology was used for the test. The cytological results were reported based on the Bethesda classification system 2001. Results: Among 200 antenatal women 57% were between 21-25 yrs of age and 18% were less than 20 years. 38% of women were less than 20 years of age at the time of beginning of sexual activity. 56% were primi gravida and others were multi gravida. 95.5 % of women were literate. 89% of women were unaware of Pap smear test. Among the 200 Pap smear reports, 23% were normal, 55.5% nonspecific inflammatory changes, 8.5% Candida infection and 13% bacterial vaginosis. None were reported with premalignant changes. Conclusions: In a population where people do not undergo Pap test due to varied reasons, antenatal Pap test not only provides an excellent opportunity to screen and create awareness for further screening, also helps detect genital infections.